Building the Next Generation of Maine Leaders: Learning from the Leadership of Mary Cathcart - Silka, Linda (Maine Policy Review, 2018)
Linda Silka reflects on Mary Cathcart’s work helping build the next generation of Maine leaders through Maine NEW (National Education for Women) Leadership, a bipartisan training for college women to help them reach their full civic potential.